Advice for working moms - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2021)
"Working moms are pulled in all directions. Find the path that works for you. Your kid gets sick, so you leave work early-again. You're an expert at driving the carpool line and setting up for the morning meeting. You missed out on another stretch assignment because you don't have time. It's assumed you'll bake the treats for the fundraiser-and man the table. As a working mother you often draw the short straw. You carry most of the burden of caregiving and household chores-and your career suffers because of it. Bosses and coworkers assume that since you're focused on your family, you don't prioritize work, and they give crucial opportunities to those around you. Advice for Working Moms can help you alleviate this stress. Drawing on the wisdom of experts and parents alike, it will help you strike the right balance between family and work, all while navigating the long-standing bias against mothers and, more broadly, women in the workforce. You'll learn to: establish the boundaries you need at home and at work, negotiate flextime, time off, and maternity leave, facilitate your return to work after taking time off for caregiving, combat the "motherhood penalty", negotiate a more equal division of labor at home with your partner, say no to "office housework" and other menial tasks at work"--
Introduction: A mother's work is never done -- get the help and support you need / Daisy Dowling, series editor -- Section 1. Mirror, mirror, on the wall -- acknowledge your emotions and stress points: Overwhelmed? How to deal with "doing it all" -- feel more competent, calm, and in control / Daisy Dowling -- Let go of working-mom guilt -- rock your "world's okayest mom" mug / Sheryl Zeigler -- Understanding your identity as a (new) working mother -- rethink how you view success-and yourself / Janna Koretz -- Section 2. Mommy tracked -- keep your career in check: How to identify a family-friendly employer -- before you take the job / Suzanne Brown -- Make your work more meaningful / Amy Gallo -- "Office housework" gets in our way -- stop doing tasks that are invisible and underappreciated / Deborah M. Kolb and Jessica L. Porter -- 4 questions to help women navigate the second half of their careers -- empty nesters, it's your time to shine / Palena Neale -- Section 3. Give me a break -- navigate your maternity leave and professional pauses: Planning maternity or family leave -- a guide -- people have babies; they get sick. It's normal / Rebecca Knight -- What nursing moms need to know about pumping during work travel -- you don't have to dump your liquid gold / Julia Beck -- How to transition into a professional break -- and set yourself up for success when you return / Daisy Dowling -- Section 4. 'A' for effort -- handling childcare and school commitments: Making a plan for childcare-and uncertainties -- think through a Plan A, Plan B, and Plan G / Avni Patel-Thompson -- How to manage the demands of school-age kids -- be a part of your child's education (without the stress) / Daisy Wademan Dowling -- When your boss doesn't respect your family commitments -- be upfront-and empathetic / Rebecca Knight -- Establishing your unique parenting posse -- find and set up a family
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 15, 2021).
WorldCat record variable field(s) change: 050
Keywords: Working mothers; Parenting; Work-life balance; Sex discrimination in employment; Sex discrimination against women; Parenting; Sex discrimination against women; Sex discrimination in employment; Work-life balance; Working mothers; elektronické knihy; electronic books